Analisis Pengembangan Usaha pada Roemah Jumpoetan Palembang Menggunakan Analisis SWOT - Putri Lidiya Mauna Tia Silvia; Dewi Fadila; Paisal Paisal (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the internal and external conditions of Roemah Jumpoetan Palembang using SWOT analysis and to formulate appropriate business development strategies to support business sustainability and competitiveness. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, questionnaires, documentation, and literature review. Data analysis was conducted using the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), and SWOT matrices to identify the strengths, weaknesses, opportunities, and threats faced by the company. The results showed that Roemah Jumpoetan Palembang obtained an IFAS score of 3.427 and an EFAS score of 3.617. Based on the analysis, the company was positioned in Quadrant I with coordinates of (0.467; 0.044), indicating a Growth-Oriented Strategy. This position demonstrates that the company possesses dominant internal strengths and external opportunities that can support aggressive business development. Therefore, the Strengths-Opportunities (SO) strategy should be prioritized. This strategy can be implemented by leveraging the company’s strengths to optimize market opportunities, improving promotional activities, expanding marketing networks, and continuously developing products. These efforts are expected to strengthen the company’s competitiveness, increase market reach, and support the long-term sustainability of Roemah Jumpoetan Palembang.